First record of the genus Physaloptera sp. (Nemata: Physalopteridae) in scats from coyote, Canis latrans in Chihuahua, México - Alvarez-Cordova, Fernando; Fernández, Jesús A.; Martínez-Salazar, Elizabeth A.; Rosas-Valdez, Rogelio (THERYA, 2019)
The knowledge of the helminth parasites of Canis latrans from Mexico is scarce. This study 23 scats of C. latrans were collected and examined to identify alimentary items between April and September of 2018, at the rancho experimental Teseachi of the Universidad Autónoma de Chihuahua, in Namiquipa, Chihuahua, México. Three nematode specimens of Physaloptera sp. were found and identified by morphology. This endoparasite is reported for the first time in scats of C. latrans for the state of Chihuahua.